(untitled) (Journal of Information Technologies in Education (ITE), 2009)
An iterative algorithm used with variable block size of public key encryption, multiple 32-m bits. Encrypt text runs in steps. As cryptographic primitives are used: stochastic scrolling block, bi-directional sliding coding, nonlinear and stochastic substitution permutation-adjustment elements of the elements of the block. The cryptotransformers of each 256-bit block is under the governance leniem individual block key, which varies depending on the encrypted data and secret round key.